2021
DOI: 10.32508/stdjns.v5i3.1071
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents of the whole plant of PHLOGACANTHUS TURGIDUS (FUA EX HOOK.F.) LINDAU

Abstract: The genus Phlogacanthus belongs to the family Acanthaceae and consists of more than 49 species, These species are widespread in tropical and subtropical zones such as Bangladesh, Bhutan, China, Indonesia, India, Myanmar and Vietnam. In Vietnam, the genus contains about 06 species. The extracts from some species in this genus have been evaluated for biological activities as analgesic, antiinflammatory, antimicrobial, antioxidant, antihyperglycemic and cytotoxic activities. In this study, the whole plant of Phlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…For instance, turgidol, a new compound, together with 5 known triterpenoids such as lupenone, lupeol, betulin, taraxer and betulinic acid were obtained from the chloroform extract of Phlogacanthus turgidus (9). Similarly, 6 chemical components of P. turgidus was identified in the ethyl acetate extract, including one derivative of phenylethanoid glycosides (martynoside), one lignan ((+)-syringaresinol), 2 steroids (bsitosterol and daucosterol) and two norisoprenoids ((+)-dehydrovomifoliol and (3S,5R,6R,7E,9S)megastiman-7-ene-3,5,6,9-tetrol) (10). Studies also demonstrated that Phlogacanthus pulcherrimus had the content of nutrition (protein, fat, fiber and moisture) and mineral (calcium, sodium, potassium, magnesium, chromium and iron) (11).…”
Section: Chemical Compositions Of Acetone Extract Of P Cornutusmentioning
confidence: 99%
“…For instance, turgidol, a new compound, together with 5 known triterpenoids such as lupenone, lupeol, betulin, taraxer and betulinic acid were obtained from the chloroform extract of Phlogacanthus turgidus (9). Similarly, 6 chemical components of P. turgidus was identified in the ethyl acetate extract, including one derivative of phenylethanoid glycosides (martynoside), one lignan ((+)-syringaresinol), 2 steroids (bsitosterol and daucosterol) and two norisoprenoids ((+)-dehydrovomifoliol and (3S,5R,6R,7E,9S)megastiman-7-ene-3,5,6,9-tetrol) (10). Studies also demonstrated that Phlogacanthus pulcherrimus had the content of nutrition (protein, fat, fiber and moisture) and mineral (calcium, sodium, potassium, magnesium, chromium and iron) (11).…”
Section: Chemical Compositions Of Acetone Extract Of P Cornutusmentioning
confidence: 99%